Using Pet Food as the Subject to Investigate the Effectiveness of Whole-Genome Sequencing in the Authentication of Highly Processed Complex Food - Zhu, Xuechen; Alden, Emily N.; Edwards, Jeremy S. (ACS food science & technology, 2023)
DNA-based tests are broadly used in food authentication. Whole-genome sequencing (WGS), in theory, can do a comprehensive inspection on all DNA-based species in a sequencing library. This method has been employed to analyze ingredients in food samples. However, it has not been examined with highly processed complex foodstuff. In contrast to the considerable effort on human food, tests on the authenticity of pet food are still lacking, though pet food safety has become a shared concern. In the present study, we tested lab-made artificial samples and manufactured pet food samples using WGS. The results demonstrated that WGS is a powerful detection to identify species in highly processed complex food and, on the other hand, revealed it cannot be used as a reliable quantification approach. Our test detected DNA of undeclared ingredients in all tested pet food samples, entailing improvements of regulation and quality control in American pet food industry.